2007
DOI: 10.1111/j.1360-0443.2007.02008.x
|View full text |Cite
|
Sign up to set email alerts
|

Personality differences in monozygotic twins discordant for cannabis use

Abstract: Aims To explore the association between cannabis and personality scores when genetic background and shared environment are controlled for. Design The co-twin control design. This design provides a powerful method for controlling for the effects of potentially confounding familial factors that may act to predispose subjects both to cannabis use and a particular personality profile. Participants 118 monozygotic twin pairs discordant for cannabis use. Measurements Data on personality and cannabis use were obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…A meta-analysis of Big Five personality traits and alcohol involvement (Malouff, Thorsteinsson, Rooke, & Schutte, 2007) showed that low conscientiousness, low agreeableness, and high neuroticism were related to numerous dimensions of alcohol use; this mirrored findings from a meta-analysis examining tobacco use (Malouff, Thorsteinsson, & Schutte, 2006). Furthermore, research on monozygotic twins discordant for cannabis involvement has shown cannabis initiation to be associated with higher levels of neuroticism (Vink, Nawijn, Boomsma, & Willemsen, 2007). Previous work has considered personality risk separately for these substances.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of Big Five personality traits and alcohol involvement (Malouff, Thorsteinsson, Rooke, & Schutte, 2007) showed that low conscientiousness, low agreeableness, and high neuroticism were related to numerous dimensions of alcohol use; this mirrored findings from a meta-analysis examining tobacco use (Malouff, Thorsteinsson, & Schutte, 2006). Furthermore, research on monozygotic twins discordant for cannabis involvement has shown cannabis initiation to be associated with higher levels of neuroticism (Vink, Nawijn, Boomsma, & Willemsen, 2007). Previous work has considered personality risk separately for these substances.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic factors influencing cannabis use overlap with those influencing use of other illicit drugs, although there are also specific genetic factors influencing use of each particular drug [31,48,53–55]. The general genetic vulnerability to drug use could be related to genes underlying personality characteristics such as novelty seeking [56–59], to biochemical attributes [60] or to psychiatric vulnerability [61,62].…”
Section: Discussionmentioning
confidence: 99%
“…Most of them participate in longitudinal studies of health, lifestyle and personality. For this study we focused on the data from the 2000 survey (Vink & Boomsma, 2008; Vink, Nawijn, Boomsma, & Willemsen, 2007), which was completed by 4609 twins. We selected participants between 21 and 40 years (N=3115).…”
Section: Methodsmentioning
confidence: 99%